Crime Salience and Public Willingness to Pay for Child Saving and Juvenile Punishment. (May 2016) - Baker, Thomas; Cleary, Hayley M. D.; Pickett, Justin T.; Gertz, Marc G.
Public policy in the area of youth crime has periodically shifted back and forth between punishment and child saving. Generally, scholars believe that public opinion and youth justice policies are linked. It is also believed that crime salience—fear and perceived risk of victimization—is linked to public opinion about youth sanctions. To test these widely held beliefs, this study examines public opinion about youth justice policies by exploring the impact of crime salience on public support for child saving versus youth punishment. This study expands on prior literature by also considering the public's willingness to pay (WTP) for the youth justice policies they prefer. Results indicate that fear increases punitiveness, WTP for youth justice policies generally, and, more specifically, the WTP for youth punishment. However, fear does not affect the public's WTP for child saving. Limitations and suggestions for future research are discussed.